Mapping Research Trends and Future Directions in Computer-Assisted Language Learning: A Bibliometric Analysis (2009–2023) - Ziman Liu (Ilmu Inovasi Nusantara, 2026)
Computer-Assisted Language Learning (CALL), an interdisciplinary field integrating information technology and linguistics, has emerged as a prominent focus in second-language acquisition research. The primary problem addressed in this study is the lack of a comprehensive mapping of research trends, thematic focuses, and developmental trajectories of CALL over the past fifteen years, particularly in the context of rapid advancements in artificial intelligence. Therefore, the objective of this study is to identify research hotspots, explore developmental patterns, and examine future trends in CALL research at both international and domestic levels. This study adopts a bibliometric approach, utilizing CiteSpace to analyze relevant literature retrieved from the Web of Science Core Collection and the China National Knowledge Infrastructure (CNKI) databases, covering the period from 2009 to 2023. The analysis focuses on keyword co-occurrence, citation networks, and cluster mapping to reveal the structural and thematic evolution of CALL research. The findings indicate that integrating emerging technologies—such as artificial intelligence, virtual reality, ubiquitous learning, flipped classrooms, and automated assessment—has significantly transformed the learning environment, pedagogical strategies, and instructional methods in foreign language education. Furthermore, the research focus has gradually shifted from technology adoption to deeper pedagogical integration. However, a notable gap remains in effectively bridging theoretical frameworks with practical implementation in language teaching contexts. The implications of this study highlight the need to develop more contextually grounded, adaptive, and theory-driven CALL models, as well as to foster interdisciplinary collaboration to enhance language learning effectiveness in the digital era. Additionally, this study provides strategic insights for guiding future CALL research, particularly within domestic academic contexts